2020
DOI: 10.1038/s41598-020-73257-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel 199 base pair NEFH promoter drives expression in retinal ganglion cells

Abstract: Retinal ganglion cells (RGCs) are known to be involved in several ocular disorders, including glaucoma and Leber hereditary optic neuropathy (LHON), and hence represent target cells for gene therapies directed towards these diseases. Restricting gene therapeutics to the target cell type in many situations may be preferable compared to ubiquitous transgene expression, stimulating researchers to identify RGC-specific promoters, particularly promoter sequences that may also be appropriate in size to fit readily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…We identified that AAV2 carrying CBA-and CMV promoters had ubiquitous expression in retinal cell types, moderate transgene expression and a relatively low expression efficacy compared to the other investigated promoters. The broad expression pattern by CMV in the retina has been observed before [13,26,27,32,88,89]. Furthermore, our finding that RGCs only make up 20-25% of the transduced cells is also consistent with a previous study that quantified the cellular tropism using this AAV serotype and promoter [32].…”
Section: Promoter Size Referencesupporting
confidence: 91%
See 2 more Smart Citations
“…We identified that AAV2 carrying CBA-and CMV promoters had ubiquitous expression in retinal cell types, moderate transgene expression and a relatively low expression efficacy compared to the other investigated promoters. The broad expression pattern by CMV in the retina has been observed before [13,26,27,32,88,89]. Furthermore, our finding that RGCs only make up 20-25% of the transduced cells is also consistent with a previous study that quantified the cellular tropism using this AAV serotype and promoter [32].…”
Section: Promoter Size Referencesupporting
confidence: 91%
“…Neurofilament light polypeptide 2693 bp [25] Neurofilament heavy polypeptide 2251 and 2501 bp a [26,27] Doublecortin 2359 bp [29] Phosphodiesterase 6H 2005 bp [30] Purkinje cell protein 2 1652 bp [31] Gamma-synuclein promoter 1450 and 953 bp a [32,33] Interphotoreceptor-binding protein 1300 bp [34] Short promoter variant of glial fibrillary acidic protein 694 bp [136] Monocyte chemo attractant protein-1 560 bp [36] Short promoter variant of mouse cone arrestin 521 bp [37] Short promoter variant of human neurofilament heavy polypeptide 199 bp [27] bp base pair.…”
Section: Promoter Size Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the cell-specific tropisms of TV and IVT administration of AAV-PHP.eB-CMV-EGFP were similar ( Figures 1 and 2 ) to each other and to that of IVT AAV2/2-CMV-EGFP, a serotype commonly used for IVT delivery to RGCs. 18 , 37 , 38 , 39 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…The evolution of AAV technology continues and is hallmarked by the frequent emergence of new and promising AAV serotypes. For example, systemic delivery of a gene-replacement therapy with AAV-PHP.B (the parental serotype of AAV-PHP.eB) provided significant benefit in an Ndufs4 knockout mouse model of Leigh syndrome, 59 where previous attempts using AAV1 63 and AAV2/9 64 serotypes resulted in less improvement. As such, the utility of AAV-PHP.B may represent a significant step toward the clinic for Leigh syndrome.…”
Section: Discussionmentioning
confidence: 99%